До питання про формування всеросійського ринку: український контекст (друга половина ХVІІ ст.) - Гуржій, О. (Український історичний журнал, 2022)
Мета статті полягає у висвітленні конкурентної боротьби українців за зарубіжні
ринки у другій половині ХVІІ ст. Методологія дослідження оперта на принципи історизму
й детермінізму. Застосовано як загальнонаукові (системного аналізу, синтезу, аналогії,
узагальнення), так і спеціальні історичні (критичного опрацювання та зіставлення джерел,
компаративності, проблемно-хронологічний) методи. Наукова новизна. Вперше порушується
питання про правомірність тверджень істориків-попередників щодо функціонування
всеросійського ринку у зазначений період і переосмислюється роль українців у цьому процесі.
Висновки. Міжнародна ситуація другої половини ХVІІ ст. зумовила цілий ряд кризових
економічних і суспільно-політичних явищ у Речі Посполитій та Українській державі, котрі,
проте, відкрили сприятливі перспективи для Московії в галузі торгівлі. Водночас торгівельні
інтереси українців уряди багатьох країн не брали до уваги. Конкурентна боротьба у цій галузі
спонукала торгових людей Гетьманщини шукати й освоювати нові шляхи та ринки для реалізації
своєї продукції, зокрема в напрямках Угорщини, Молдавії, Волощини, Прибалтики,
Сходу. The purpose of the paper is to cover the competitive struggle of Ukrainians for foreign
markets in the second half of the seventeenth century. The research methodology is based on
the principles of historicism and determinism. Both general scientific (system analysis, synthesis,
analogy, generalization) and special historical (critical analysis and comparison of sources,
comparability, problem-chronological) methods are used. The scientific novelty. For the first
time, the question of the legitimacy of the claims of previous historians about the functioning
of the all-Russian market at that time is raised and the role of Ukrainians in this process is
reconsidered. Conclusions. Separating from the Polish-Lithuanian Commonwealth during the
National Revolution, Ukraine acquired several fundamentally important economic problems.
One of them was the possibility of free maritime trade. In particular, in the north the territory
of the first covered part of the Baltic coast, and in the south the Ukrainian lands occupied by it
had access to the Black Sea. Although decentralized, politically and economically weakened Poland
could not fully guarantee trade across the Baltic Sea, where various foreign merchants, especially
Germans, were determined to be powerful competitors, Ukrainians used this path. After leaving
the Commonwealth, the situation in this matter, of course, became much more complicated.
On the Black Sea coast, the power of Turks and Tatars, who were constantly at war with Muscovy,
increased. By joining the Russian state, Ukrainian merchants formally joined the only seaside
port in the distant and inhospitable Arkhangelsk, through which Muscovy conducted the most
part of its foreign trade. However, nobody expected the new competitors with opened arms here.
The road through Pskov and Novgorod to Narva, which was under Swedish rule, did not make
things any easier. The division of Ukraine into several parts, mainly on the left bank and the right
bank, greatly complicated domestic and foreign trade; merchants were defenceless against the
authorities of that countries through which they passed. The local armed conflicts caused problems
as well. The international situation in the second half of the seventeenth century caused a number
of crisis economic and socio-political phenomena in the Polish-Lithuanian Commonwealth and
the Ukrainian state, which nevertheless opened favourable prospects for Muscovy in the field
of trade. At the same time, the trade interests of Ukrainians were not taken into account by the
governments of many foreign countries. Competitive struggle in this area prompted the merchants
of the Hetmanate to seek and establish new ways and markets for the sale of their products, in
particular in Hungary, Moldaviia, Wallachia, the Baltic States and the East.